NIMG-03. PREOPERATIVE DEXAMETHASONE LEADS TO SIGNIFICANT REDUCTIONS IN PERITUMORAL EDEMA FOR PATIENTS WITH BRAIN METASTASES. (14th November 2022) - Tan, Hao; Bowden, Stephen; Cheaney, Barry; Richie, Emma; de Leeuw, Charles; Wood, Matthew; Raslan, Ahmed; Han, Seunggu; Barajas, Ramon
Abstract: INTRODUCTION: Corticosteroids are commonly used preoperatively in patients with brain metastases to mitigate symptoms related to vasogenic peritumoral edema (PTE). Though these tumors are highly prevalent, surprisingly few studies have examined the effect of steroids on PTE evident on MRI. We investigated whether steroid administration was associated with greater reduction in PTE in brain metastasis patients compared to steroid-naïve patients. Additionally, we sought to determine if PTE reductions reflect preoperative neurologic improvement and whether an association existed between change in PTE and preoperative steroid dosing. METHODS: We identified 27 patients with brain metastases and two pre-operative MRIs—one pre- and one post-steroid administration. PTE and tumor volume was calculated from FLAIR or T2 sequences using 3D Slicer. PTE was quantified with Edema Index (EI). Pertinent demographic, clinical, and dexamethasone dosing data were extracted from patient charts. Descriptive statistics were performed to compare demographic, clinical, and radiographic data between patient strata. A Pearson's R correlation was performed to assess for an association between percent change in PTE and dexamethasone dosing. All statistics were computed in R with a threshold of α= 0.05. RESULTS: Patients that received preoperative dexamethasone demonstrated significantly greater percent reduction in PTE compared to their steroid naïve counterparts (p = 0.02). This finding was despite similar time elapsed between MRI studies across both groups. Similar PTE changes were observed in those with and without preoperative neurologic improvement. No significant correlation was found between percent-change in PTE and dexamethasone dosing. CONCLUSIONS: We are the first to demonstrate that preoperative dexamethasone administration significantly reduces PTE in patients with brain metastases when compared to a steroid naïve reference group. Curiously, a superior reduction in PTE was not reflective of neurologic improvement. The clinical significance of this merits further study.